Reactive Stepping Responses Mediated by Predictable Manual Waist-Pull Perturbations are Associated with Fall History in Older Adults - Rachana Gangwani; Tanvi Bhatt; Richard Bohannon; Louis DePasquale (Journal of Aging Research And Healthcare, 2020)
Background and Purpose The ability to respond effectively to perturbations is a key element of reactive postural control and is a crucial mediator of falls. Several studies exist in the literature that determine older adults’ responses to perturbations, however those studies typically involve procedures that lack objectivity or applicability outside a laboratory. A study involving waist-pull perturbations with a spring-scale (SS) is an exception. In that study, fall history was most accurately differentiated by a reactive stepping response to a perturbing force of 10% total body weight. Using data from that study, we retrospectively examined the association between fall history and the number of steps accompanying a SS perturbing force of 10% total body weight in older adults. For perspective, the association of fall history with Timed-Up-and-Go (TUG) and single limb stance (SLS) times was also determined. Methods Fifty-eight healthy older adults (mean age = 80.7 years) participated in the study. Their 2-year fall history (yes, no) was recorded. All participants underwent SS testing with one-pound incremental, horizontal sagittal plane manual waist-pull perturbations. The number of steps in response to perturbation with 10% total body weight was recorded; TUG and SLS tests were performed. Associations between variables were examined using Spearman (rank-biserial) correlations. Results The median number of steps for fallers was 5 in both anterior and posterior directions. For non-fallers, the median number of steps was 1 and 2 in the anterior and posterior directions, respectively. The significant correlations between fall status and number of steps were 0.772 and 0.813 for the anterior and posterior directions, respectively. Similarly, the significant correlations between fall status and balance tests were 0.722 and -0.456 for the TUG and the SLS, respectively. Conclusions The number of steps accompanying waist-pull perturbations with forces of 10% of body weight were highly explanatory of experiencing a fall during the preceding 2 years.
Keywords: Balance